Diving in the minds of recruiters: What triggers gender stereotypes in hiring? - Hannah Van Borm; Stijn Baert (Global Labor Organization (GLO), 2022)
We investigate the drivers of gender differentials in hiring chances. More concretely, we test (i) whether recruiters perceive job applicants in gender stereotypical terms when making hiring decisions and (ii) whether the activation of these gender stereotypes in recruiters' minds varies by the salience of gender in a particular hiring context and the gender prototypicality of a job applicant, as hypothesised in Ridgeway and Kricheli-Katz (2013). To this end, we conduct an innovative vignette experiment in the United States with 290 genuine recruiters who evaluate fictitious job applicants regarding their hireability and 21 statements related to specific gender stereotypes. Moreover, we experimentally manipulate both the gender prototypicality of a job applicant and the salience of gender in the hiring context. We find that employers perceive women in gender stereotypical terms when making hiring decisions. In particular, women are perceived to be more social and supportive than men, but also as less assertive and physically strong. Furthermore, our results indicate that the gender prototypicality of job applicants moderates these perceptions: the less prototypical group of African American women, who are assumed to be less prototypical, are perceived in less stereotypical terms than white women, while some stereotypes are more outspoken when female résumés reveal family responsibilities.
Keywords: J71; J16; J15; J13; J24; 330; hiring; gender discrimination; stereotypes; race; motherhood